Relasi Kuasa Ulama Sufi dan Negara dalam Kultur-Budaya Politik Indonesia - Rubaidi Rubaidi (Institut Agama Islam Negeri Kendari, 2021)
This article examines the critical role of the dimensions of Sufism represented by Sufi ulama in the public sphere (political power) state, either directly or indirectly. In Indonesian historicity, the relationship between Sufi ulama and the state has lasted centuries, even to the modern era. In political theory, there is a